Desorption Electrospray Ionization Mass Spectrometry Assay for Label‐Free Characterization of SULT2B1b Enzyme Kinetics. (10th February 2022) - Kulathunga, Samadhi C.; Morato, Nicolás M.; Zhou, Qing; Cooks, R. Graham; Mesecar, Andrew D.
Abstract: The sulfotransferase (SULT) 2B1b, which catalyzes the sulfonation of 3β‐hydroxysteroids, has been identified as a potential target for prostate cancer treatment. However, a major limitation for SULT2B1b‐targeted drug discovery is the lack of robust assays compatible with high‐throughput screening and inconsistency in reported kinetic data. For this reason, we developed a novel label‐free assay based on high‐throughput (>1 Hz) desorption electrospray ionization mass spectrometry (DESI‐MS) for the direct quantitation of the sulfoconjugated product (CV<10 %; <1 ng analyte). The performance of this DESI‐based assay was compared against a new fluorometric coupled‐enzyme method that we also developed. Both methodologies provided consistent kinetic data for the reaction of SULT2B1b with its major substrates, indicating the affinity trend pregnenolone>DHEA>cholesterol, for both the phospho‐mimetic and wild‐type SULT2B1b forms. The novel DESI‐MS assay developed here is likely generalizable to other drug discovery efforts and is particularly promising for identification of SULT2B1b inhibitors with potential as prostate cancer therapeutics. Abstract : The first application of a novel label‐free enzymatic assay based on high‐throughput desorption electrospray ionization mass spectrometry is demonstrated for the kinetic characterization of the sulfotransferase (SULT) 2B1b, a potential target for prostate cancer treatment. The results of this method, including the behavior of SULT2B1b against its three major substrates, were in agreement with those of a new fluorometric coupled‐enzyme assay.